Strategi Peningkatan Daya Saing UMKM Terhadap Perdagangan Internasional - Annisa Cindy Maurina; R Yuniardi Rusdianto (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
In various efforts to improve the economy of the Indonesian people, the role of MSME actors is considered very important to support and sustain people's lives. Many sectors have succeeded in encouraging the government to build structure and development in improving the Indonesian economy by providing employment and fully supporting MSME actors to further develop. The position of MSMEs itself is very undoubted because they managed to survive and become the driving force of the Indonesian economy during the crisis some time ago. Likewise, the influence of globalization can lead to very tight competition in export-import activities or international trade, so that economic growth and the welfare of some people can be achieved broadly and evenly. With the government's role in supporting the competitiveness strategy and development of MSMEs, new features are needed.